Challenges of crisis management in educational institutions of the Republic of Croatia - Kedačić-Buzina, Katarina; Klarin, Tomislav (Crisis Management Days, 2024)
In recent years, educational institutions in Croatia have increasingly encountered various crises, sparking heightened concerns among stakeholders, particularly institution principals, regarding the challenges of crisis management. This paper presents the findings of a qualitative research study that delved into the perspectives of stakeholders within educational institutions regarding crisis management and crisis communication, conducted through interviews. The research aimed to elucidate the characteristics of crisis situations, as well as the potential and constraints associated with implementing crisis management and crisis communication strategies in Croatian educational institutions. The results of the study indicate that the current crisis management system is inefficient. While certain protocols and regulations exist at the national level for addressing specific crisis situations, their implementation and effectiveness largely hinge on institutional leadership. Consequently, while opportunities for implementing crisis management strategies in educational institutions have been identified, various limitations have also been acknowledged. INTRODUCTION Crisis is a concept encountered almost daily, manifesting in various forms and yielding diverse consequences. Successfully navigating and responding to different types of crises hinges on effective crisis management systems. Such systems encompass a series of activities geared towards preventing crises, managing them effectively, and ultimately facilitating recovery. The efficacy of crisis management is contingent upon an understanding of key crisis characteristics, including threat, urgency, and uncertainty. According to numerous authors, crisis communication plays a pivotal role in crisis resolution. Inevitable in crisis situations, crisis communication can be proactive or reactive. Beyond crisis resolution, effective crisis communication can bolster an organization’s reputation. Despite being perceived as sanctuaries, educational institutions have demonstrated vulnerability to escalating social, health, and financial pressures in the past decade. The global surge in both frequency and severity of school crises underscores the pressing need for the integration of crisis management into the daily administration of educational institutions. AIM The aim of this paper was primarily to determine the characteristics of crisis situations, followed by exploring the possibilities and limitations of implementing crisis management and crisis communication in educational institutions in the Republic of Croatia. RESEARCH METHODOLOGY The perspectives of stakeholders within educational institutions concerning the implementation of crisis management and crisis communication in the Republic of Croatia were investigated through semi-structured interviews. The study encompassed representatives from the Ministry of Science and Education, school principals, teaching and non-teaching staff, kindergarten educators, as well as final-year high school students and parents of children attending educational institutions. RESULTS The research findings indicate that both the national and local levels of the education system in the Republic of Croatia exhibit inefficiencies in crisis management, despite the existence of protocols and regulations outlining procedures for specific crisis situations. Educational institutions are revealed to be ill-equipped to handle crises effectively, with success largely contingent on the leadership of the institution, particularly the principals. Furthermore, the research underscores the necessity of trained personnel for crisis situations, as well as the establishment of crisis resolution teams within institutions tasked with regularly practicing pre-prepared crisis plans and communication strategies. The study identifies various opportunities for the implementation of crisis management and communication strategies, ranging from the development of clear action plans for diverse crisis scenarios to fostering effective communication across all levels of the educational hierarchy and forming crisis teams within institutions. Recognizing education as paramount, the potential for further research in the realm of crisis management and communication within Croatia’s education system is emphasized. This includes the proposal for mandatory courses in crisis management within postgraduate specialist studies for principals, as well as integration into the curriculum for early childhood educators, teachers, instructors, and educational professionals, alongside programs focused on pedagogical-psychological-didactic-methodological training. However, several limitations are identified, including a lack of theoretical-practical knowledge in crisis management, inconsistent policies, insufficient financial investment in the education system, ineffective top-down communication, and inadequate autonomy of principals in decision-making processes. Addressing these limitations will be critical in enhancing the resilience of educational institutions to crises and ensuring the safety and well-being of students and staff. CONCLUSION In recent years, educational institutions have faced a growing array of crises, navigating them to the best of their abilities. The efficacy of their crisis response hinges significantly on the marketing and communication skills of the institution’s leadership, coupled with the degree of preparedness. Numerous studies underscore the pivotal role of crisis management in successfully navigating such challenges, as it enables swift and effective responses. However, experts caution against relying solely on the existence of crisis management frameworks and theoretical models for effective crisis management. Instead, they emphasize the importance of regular practice and ongoing supplementation of crisis management strategies.